Role of Vitamins A and D in BCR-ABL Arf(−/−) Acute Lymphoblastic Leukemia - Annu, Kavya (Sci Rep, 2020)
The effects of vitamin A and/or vitamin D deficiency were studied in an Arf(−/−) BCR-ABL acute lymphoblastic leukemia murine model. Vitamin D sufficient mice died earlier (p = 0.003) compared to vitamin D deficient (VDD) mice. Vitamin A deficient (VAD) mice fared worst with more rapid disease progression and decreased survival. Mice deficient for vitamins A and D (VADD) had disease progression similar to VAD mice. Regulatory T cells, previously shown to associate with poor BCR-ABL leukemia control, were present at higher frequencies among CD4(+) splenocytes of vitamin A deficient vs. sufficient mice. In vitro studies demonstrated 1,25-dihydroxyvitamin D (1,25(OH)(2)VD(3)) increased the number of BCR-ABL ALL cells only when co-cultured with bone marrow stroma. 1,25(OH)(2)VD(3) induced CXCL12 expression in vivo and in vitro in stromal cells and CXCL12 increased stromal migration and the number of BCR-ABL blasts. Vitamin D plus leukemia reprogrammed the marrow increasing production of collagens, potentially trapping ALL blasts. Vitamin A (all trans retinoic acid, ATRA) treated leukemic cells had increased apoptosis, decreased cells in S-phase, and increased cells in G(0)/G(1). ATRA signaled through the retinoid X receptor to decrease BCR-ABL leukemic cell viability. In conclusion, vitamin A and D deficiencies have opposing effects on mouse survival from BCR-ABL ALL.